Experimental validation of a method for virtual testing of bike settings - André, C.; Lemaître, C.; Voiry, M. (Journal of Science and Cycling, 2023)
Based on our previous works, we propose a method for virtual testing of bike settings. This allows the biomechanical and aerodynamic properties of a bike setting to be assessed without having to test it in real life. We also perform an experimental validation of the method by comparing measured and simulated values of different indicators: the frontal area, the maximum knee flexion, the maximum knee extension, the hip angle closed and the hip angle open.